Immune checkpoint inhibitors and cardiovascular toxicity. Issue 9 (September 2018) - Lyon, Alexander R; Yousaf, Nadia; Battisti, Nicolò M L; Moslehi, Javid; Larkin, James
Summary: Immune checkpoint inhibitors are a new class of anticancer therapies that amplify T-cell-mediated immune responses against cancer cells. Immune checkpoint inhibitors have shown important benefits in phase 3 trials, and several agents have been approved for specific malignancies. Although adverse events from immune checkpoint inhibitors are a common occurrence, cardiotoxic effects are uncommon, but are often serious complications with a relatively high mortality. Most cardiotoxic effects appear to be inflammatory in nature. Clinical assessment of a combination of biomarkers, electrocardiography, cardiac imaging, and endomyocardial biopsy can be used to confirm a possible diagnosis. In this Review, we discuss the epidemiology of immune checkpoint inhibitor-mediated cardiotoxic effects, as well as their clinical presentation, subtypes, risk factors, pathophysiology, and clinical management, including the introduction of a new surveillance strategy.